Gabon : 2010 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Gabon. (IMF Staff Country Reports; Country Report ;, 2011)
Oil production over the last 40 years has transformed Gabon into a middle-income country; but income inequality is high, and non-commodity sectors are stagnant. Gabon is recovering from the global financial crisis. The recovery to be sustained, with downside risks from commodity prices and possible slippages in policy implementation. The fiscal stance has important implications for domestic stability. Medium-term fiscal consolidation is vital to ensuring fiscal sustainability and external competitiveness as oil production dwindles over time. The authorities have embarked on major reforms of public financial management (PFM).